JIRA 5.x Development Cookbook - Kuruvilla, Jobin (Packt Publishing, 2013)
JIRA 5.x Development Cookbook is part of Packt's Cookbook series. A Packt Cookbook contains step-by-step recipes for solutions to the most important problems you face when working with a topic. Inside this Cookbook you will find:A straightforward and easy-to-follow format. A selection of the most important tasks and problems. Carefully organized instructions for solving the problem efficiently. Clear explanations of what you did. Details for applying the solution to other situations. If you are a JIRA developer or project manager who wants to fully exploit the exciting capabilities of JIRA, then thi.